Secondary metabolites from Micromonospora sp. (G044) - Tuan, Cao Duc; Ngan, Truong Bich; Huong, Doan Thi Mai; Quyen, Vu Thi; Minh, Le Thi Hong; Murphy, Brian; Minh, Chau Van; Cuong, Pham Van (Vietnam Journal of Science and Technology, 2017)
In the course of our screening program, the EtOAc extract of a Micromonospora sp. (strain G044) from sponge Tethya aurantium of the sea of Côtô - Thanh Lân exhibited antimicrobial activity against Enterococcus faecalis, Bacillus cereus and Candida albicans. In this paper, we reported the isolation and structural elucidation of six secondary metabolites Cyclo-(Pro-Trp) (1), Cyclo-(Pro-Met) (2), Cyclo-(Pro-Val) (4), N-acetyltryptamine (3), uridine (5), and 2-phenylacetic acid (6) from the cultures broth of Micromonospora sp. (strain G044). The structures of 1 – 6 were determined by analyses of MS and 2D NMR data. All compounds were evaluated for their antimicrobial activity against a panel of clinically significant microorganisms. Compound 1 inhibited Escherichia coli with a MIC value of 128 µg/ml.